Clostridium cellulolyticum: model organism of mesophilic cellulolytic clostridia - Desvaux, M.
Clostridium cellulolyticum ATCC 35319 is a non-ruminal mesophilic cellulolytic bacterium originally isolated from decayed grass. As with most truly cellulolytic clostridia, C. cellulolyticum possesses an extracellular multi-enzymatic complex, the cellulosome. The catalytic components of the cellulosome release soluble cello-oligosaccharides from cellulose providing the primary carbon substrates to support bacterial growth. As most cellulolytic bacteria, C. cellulolyticum was initially characterised by limited carbon consumption and subsequent limited growth in comparison to other saccharolytic clostridia. The first metabolic studies performed in batch cultures suggested nutrient(s)limitation and/or by-product(s)inhibition as the reasons for this limited growth. In most recent investigations using chemostat cultures, metabolic flux analysis suggests a self-intoxication of bacterial metabolism resulting from an inefficiently regulated carbon flow. The investigation of C. cellulolyticum physiology with cellobiose, as a model of soluble cellodextrin, and with pure cellulose, as a carbon source more closely related to lignocellulosic compounds, strengthen the idea of a bacterium particularly well adapted, and even restricted, to a cellulolytic lifestyle. The metabolic flux analysis from continuous cultures revealed that (i)in comparison to cellobiose, the cellulose hydrolysis by the cellulosome introduces an extra regulation of entering carbon flow resulting in globally lower metabolic fluxes on cellulose than on cellobiose, (ii)the glucose -phosphate/glucose 6-phosphate branch point controls the carbon flow directed towards glycolysis and dissipates carbon excess towards the formation of cellodextrins, glycogen and exopolysaccharides, (iii)the pyruvate/acetyl-CoA metabolic node is essential to the regulation of electronic and energetic fluxes. This in-depth analysis of C. cellulolyticum metabolism has permitted the first attempt to engineer metabolically a cellulolytic microorganism.
Keywords: BACTERIAL METABOLISM; CELLULOSE DEGRADATION; CELLULOSOME; METABOLIC FLUX ANALYSIS; CELLULOLYTIC CLOSTRIDIA; METABOLIC ENGINEERING